Physical activity measured using wearable activity tracking devices associated with gout flares - Nada Elmagboul; Brian W. Coburn; Jeffrey Foster; Amy Mudano; Joshua Melnick; Debra Bergman; Shuo Yang; Lang Chen; Cooper Filby; Ted R. Mikuls; Jeffrey R. Curtis; Kenneth Saag (Arthritis Research & Therapy, 2020)
Abstract Objective To determine the feasibility and validity of using wearable activity trackers to test associations between gout flares with physical activity and sleep. Methods Participants with physician-diagnosed gout, hyperuricemia (≥ 6.8 mg/dl), current smartphone use, and ≥ 2 self-reported flares in the previous 6 months were enrolled. Physical activity, heart rate, and sleep data were obtained from wearable activity trackers (Fitbit Charge HR2). Daily compliance was defined by the availability of sufficiently complete activity data at least 80% of the day. Associations of weekly gout flares with sleep and activity were measured by comparing flare-related values to average sleep and steps per day. We used mixed linear models to account for repeated observations. Results Forty-four participants enrolled; 33 met the criteria for minimal wear time and flare reporting, with activity tracker data available for 60.5% of all total study days. Mean ± SD age was 48.8 ± 14.9 years; 85% were men; 15% were black; 88% were on allopurinol or febuxostat, and 30% reported ≥ 6 flares in the prior 6 months. Activity trackers captured 204 (38%) person-weeks with flares and 340 (62%) person-weeks without flares. Mean ± SD daily step count was significantly lower (p < 0.0001) during weeks with gout flares (5900 ± 4071) than during non-flare periods (6972 ± 5214); sleep however did not differ. Conclusion The pattern of wear in this study illustrates reasonable feasibility of using such devices in future arthritis research. The use of these devices to passively measure changes in physical activity patterns may provide an estimate of gout flare occurrence and duration. Trial registration NCT, NCT02855437 . Registered 4 August 2016